Theory of oscillators - Andronov, Aleksandr Aleksandrovich (Pergamon Press, 1966)
Widely considered one of the classic books on nonlinear oscillators, this comprehensive volume offers a uniquely detailed and thorough discussion of an important branch of mathematics. Indeed, for mathematicians seeking the physical foundations of the theory of nonlinear oscillations, it is a veritable encyclopedia.